Perancangan UI/UX Aplikasi Zaafer Mobile Menggunakan Metode Design Thinking - Ardelia, Adinda Abidah; Irsyad, Muhammad; Chandra, Reski Mai; Affandes, Muhammad (Jurnal Informatika Ekonomi Bisnis, 2025)
Zaafer is a company specializing in slim-fit men’s Muslim attire, operating an official e-commerce site at www.zaaferindonesia.id. After interviewing ten users who had previously shopped on the Zaafer website, we found that they did not receive real-time notifications and felt more comfortable shopping via an Android app rather than through the website. This insight motivated the design of a mobile-based Zaafer application to enhance the user experience. The relationship between user interface interactions and UX is a critical factor in application design. This study aims to design the UI/UX of the Zaafer mobile application using the Design Thinking methodology, which comprises five stages: empathize, define, ideate, prototype, and testing. Prototype testing of the Zaafer mobile app using the Single Ease Question method yielded a score of 6.33 out of 7, indicating a good rating. Based on these results, we conclude that the UI/UX design of the Zaafer mobile application is well accepted by users.